2021
DOI: 10.30589/pgr.v5i3.373
|View full text |Cite
|
Sign up to set email alerts
|

Tax Facilities through Omnibus Law Taxation: A Canon Taxation Review

Abstract: This research is a conceptual study to examine tax policy in the pandemic situation with a canon taxation perspective, namely equity, certainty, convenience, and efficiency. The study conducted by using a literature review concerning the role of Omnibus Law includes tax facilities to attract foreign investment underlining strengths and weaknesses. Data is obtained through secondary sources in the form of archival reports and previous research relevant to the research. Based on the analysis of literature studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…1. Relive the tax burden under the consideration of the subjective condition of taxpayer and the objective condition tax object; [16] 2. Tax amnesty for arrears of administrative sanctions payment, [17]by considering the efficiency of tax collection costs against the taxpayer;[18] and 3.…”
Section: Tax Facility Policy As Implementation Of Fiscal Decentraliza...mentioning
confidence: 99%
“…1. Relive the tax burden under the consideration of the subjective condition of taxpayer and the objective condition tax object; [16] 2. Tax amnesty for arrears of administrative sanctions payment, [17]by considering the efficiency of tax collection costs against the taxpayer;[18] and 3.…”
Section: Tax Facility Policy As Implementation Of Fiscal Decentraliza...mentioning
confidence: 99%
“…Tinjauan dari sisi aspek PPh, pemerintah juga akan meredefinisi bentuk usaha tetap (BUT) (Ridayati et al, 2020). Kebijakan ini merupakan strategi untuk menghindari pajak berganda sehingga celah penghindaran pajak dapat diminimalisir (Fidiana F, 2021).…”
Section: Pendahuluanunclassified
“…Several studies have analyzed tax incentives during the Covid-19 pandemic. Fidiana (2021) conducted a literature study to examine tax policy during the Covid-19 pandemic through the perspective of the taxation principles proposed by Adam Smith, which include equity, certainty, convenience, and efficiency. Okafor et al (2019) found evidence that tax incentives during the crisis positively affected small business plays a roles business continuity.…”
mentioning
confidence: 99%